Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

Polymer type drives successional structural and functional organization of plastisphere microbial networks - Kyu-Young Shim; In-Cheol Yeo; Euihyeon Lee; Hyun-Jung Kim; Kang Eun Kim; Jiezhang Mo; Youn-Jung Kim; Chang-Bum Jeong (Marine Environmental Research, 2026)

Effects of Clinostat rotation on stem morphology of Pisum Sativum - Sang-Min Kim; Jung-Hoo Kook; Jeong-In Choi; Oluwasegun Moses Ogundele; Won-Cheol Lee; Hyeon-Tae Kim (Life Sciences in Space Research, 2026)

Molecular biomarkers associated with environmental naphthalene exposure in the respiratory system - Hye-Jeong Han; Amartuvshin Baasankhuu; Bogun Kim; Angela Astrid Sekar Prameswari; Karina Kalani; Paolo Panza; Sangwoo Lee; Woo-Keun Kim; In-Geol Choi; Cheol-Hee Kim; Hyun-Taek Kim (Science of The Total Environment, 2026)

Chemical constituents of culture broth of the marine-derived fungus Towyspora aestuari and their antioxidant activity - Mungyeong Gwon; Dae-Won Ki; Dae-Cheol Choi; Ji-Yul Kim; Won-Gi Seo; Yongkuk Lee; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2025)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

High-purity Li₆PS₅Cl sulfide solid electrolytes via liquid-phase method synthesis for high-performance all-solid-state Li-ion batteries: Particle-scale analysis of formation with precursor and solvent optimization - Hyewon Jo; Bitna Kim; Byeong-Min Ahn; Youngjun Huh; Soyoung Kim; Jung Han Kim; Heetaek Park; Jun-Woo Park; Yoon-Cheol Ha; Jay Hyok Song; Je In Lee; Jun-Ho Park (Chemical Engineering Journal, 2025)

Calcium-Rich Steel Slag as a Reactive Capping Material: Effects on Hydraulic Conductivity and Nutrient Attenuation in Cohesive Intertidal Sediments - Hee-Eun Woo; Valianto Rojulun Afif; Seongsik Park; Maheshkumar Prakash Patil; Ilwon Jeong; In-Cheol Lee; Jong-Oh Kim; Kyunghoi Kim (Journal of Marine Science and Engineering, 2025)
Fine-grained intertidal sediments are typically characterized by low hydraulic conductivity and high nutrient loads, conditions that hinder biogeochemical recovery and exacerbate eutrophication. This study examined the feasibility of calcium-rich steel slag (SS) as a multifunctional capping material for improving both physical and chemical properties of cohesive sediments. Short-term (24 h) column experiments with two slag dosages (25 g and 50 g) revealed that the higher dosage (SS50) increased sediment hydraulic conductivity by 113.2%, likely through Ca2+-mediated flocculation and enhanced pore connectivity. Phosphate (PO4-P) in pore water decreased by up to 64.1%, and effluent dissolved inorganic nitrogen (DIN) declined by 62.8%, indicating combined effects of Ca-driven precipitation, adsorption, and enhanced flushing. However, SS addition also raised pore water pH (to 11.8) and lowered redox potential, leading to transient phosphate release at the effluent boundary under reducing conditions. Cation analysis confirmed Ca2+ stability and Na+ reduction, suggesting improved sediment structural integrity. The results suggest that steel slag is a promising reactive capping material capable of enhancing permeability and controlling nutrient release in cohesive coastal sediments, yet further investigation into long-term ecological effects and dosage optimization is necessary.

Valorization of coffee residues improve bioelectricity generation and benthic nutrient removal in sediment microbial fuel cells - Nurfarhana Nabila Mohd Noor; Hee-Eun Woo; In-Cheol Lee; Jong-Oh Kim; Kyunghoi Kim (Biomass and Bioenergy, 2025)

New dimeric 1,3-dihydroisobenzofuran from culture broth of Fennellia flavipes - Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Ultrathin Two-Dimensional Ordered Porous Carbon Host with Atomically Dispersed Electrocatalytic Sites toward High Volumetric Energy Lithium-Sulfur Battery - Won-Gwang Lim; Minkyeong Ban; Kyu In Shim; Jinkyu Park; Seongbeen Kim; Seongseop Kim; Seoa Kim; Cheol-Young Park; Jeong Woo Han; Jinwoo Lee (Chemical Engineering Journal, 2024)

Three undescribed dimeric ferulates from the culture broth of Phellinus linteus and their dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Won-Gi Seo; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Utilization of coffee waste as a sustainable feedstock for high-yield lactic acid production through microbial fermentation - Seulbi Kim; Jong-Cheol Kim; Yeong Yeol Kim; Jung Eun Yang; Hee Min Lee; In Min Hwang; Hae Woong Park; Ho Myeong Kim (Science of The Total Environment, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

CFD Analysis of Microplastic Transport over the Slopes - Le Duc Quyen; Young-Gyu Park; In-cheol Lee; Jun Myoung Choi (Journal of Marine Science and Engineering, 2024)
Microplastics, ubiquitous in our environment, are significantly impacted by the hydrodynamic conditions around them. This study utilizes CFD to explore how various breaker types influence the dispersion and accumulation of microplastics in nearshore areas. A special focus is given to the impact of wave dynamics and particle size, particularly on buoyant microplastics in spilling breakers. It was discovered that spilling breakers, common on gently sloping seabeds, encourage broad dispersion of microplastics, notably for smaller-sized particles. Plunging breakers exhibit a similar pattern but with less dispersion and an initial forward movement of neutral and heavy particles. Surging breakers feature minimal dispersion and a distinct oscillatory motion. It has been observed that medium-sized particles with a 1 mm diameter in this work exhibit the most substantial forward movement, likely due to an optimal balance between inertia and viscosity, enabling an effective response to wave momentum. Larger particles, influenced mainly by inertia, tend to show less dispersion and advection. Meanwhile, smaller particles, more affected by viscosity, demonstrate greater dispersion, interacting extensively with wave-induced turbulence. This study reveals the significance of inertia in the behavior of microplastics over slopes, emphasizing the importance of considering inertial effects for precise modeling of microplastic movement in nearshore areas.

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Field experiments on chemical and biological changes of thin-layer oyster shells capping sediments in dense aquaculture area - Hee-Eun Woo; Ilwon Jeong; Jong-Oh Kim; Young-Ryun Kim; In-Cheol Lee; Kyunghoi Kim (Environmental Research, 2023)

Chemical constituents of the culture broth of Dentipellis fragilis and their anti-inflammatory activities - Dae-Won Ki; Chae-Won Kim; Dae-Cheol Choi; Gun-Woo Oh; Thi-Phuong Doan; Ji-Yul Kim; Won-Keun Oh; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry, 2023)

Development of high-performance organic photodetectors by understanding origin of dark current density with synthesis of photoconductive polymers - WonJo Jeong; Jinhyeon Kang; Dongchan Lee; Cheol Shin; Hyungju Ahn; Chan So; Jong Ho Won; Dae Sung Chung; Shinuk Cho; In Hwan Jung (Chemical Engineering Journal, 2023)

Coinfection with porcine epidemic diarrhea virus and Clostridium perfringens type A enhances disease severity in weaned pigs - Duri Lee; Guehwan Jang; Kyeng-Cheol Min; Inn Hong Lee; Hokeun Won; In-Joong Yoon; Sang Chul Kang; Changhee Lee (Archives of Virology, 2023)

Deletion of pentad residues in the N-terminal domain of spike protein attenuates porcine epidemic diarrhea virus in piglets - Guehwan Jang; Kyeng-Cheol Min; Inn Hong Lee; Hokeun Won; In-Joong Yoon; Sang Chul Kang; Changhee Lee (Veterinary Microbiology, 2023)

Electronic structure reconfiguration of nickel–cobalt layered double hydroxide nanoflakes via engineered heteroatom and oxygen-vacancies defect for efficient electrochemical water splitting - Kai Chen; Yong-Hua Cao; Sunny Yadav; Gyu-Cheol Kim; Zheng Han; Wenmeng Wang; Wei-Jin Zhang; Vandung Dao; In-Hwan Lee (Chemical Engineering Journal, 2023)

Effects of edible insect extracts on the antioxidant, physiochemical, and microbial properties of Tteokgalbi during refrigerated storage - Hae In Yong; Tae-Kyung Kim; Ji Yoon Cha; Jae Hoon Lee; Min-Cheol Kang; Samooel Jung; Yun-Sang Choi (Food Bioscience, 2023)

Peptides inhibiting angiotensin-I-converting enzyme: Isolation from flavourzyme hydrolysate of Protaetia brevitarsis larva protein and identification - Jae Hoon Lee; Tae-Kyung Kim; Hae In Yong; Ji Yoon Cha; Kyung-Mo Song; Hyo Geun Lee; Jun-Geon Je; Min-Cheol Kang; Yun-Sang Choi (Food Chemistry, 2023)

A Comparative Study of an Anti-Thrombotic Small-Diameter Vascular Graft with Commercially Available e-PTFE Graft in a Porcine Carotid Model - Kyo Seon Lee; Mukhammad Kayumov; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Yun-Jin Jeong; Dong-Weon Lee; Jun-Kyu Park; Chan-Hee Park; Cheol-Sang Kim; Francis O. Obiweluozor; In-Seok Jeong (Tissue Engineering and Regenerative Medicine, 2022)
Background: We have designed a reinforced drug-loaded vascular graft composed of polycaprolactone (PCL) and polydioxanone (PDO) via a combination of electrospinning/3D printing approaches. To evaluate its potential for clinical application, we compared the in vivo blood compatibility and performance of PCL/PDO + 10%DY grafts doped with an antithrombotic drug (dipyridamole) with a commercial expanded polytetrafluoroethylene ( e -PTFE) graft in a porcine model. Methods: A total of 10 pigs (weight: 25–35 kg) were used in this study. We made a new 5-mm graft with PCL/PDO composite nanofiber via the electrospinning technique. We simultaneously implanted a commercially available e -PTFE graft ( n = 5) and our PCL/PDO + 10%DY graft ( n = 5) into the carotid arteries of the pigs. No anticoagulant/antiplatelet agent was administered during the follow-up period, and ultrasonography was performed weekly to confirm the patency of the two grafts in vivo . Four weeks later, we explanted and compared the performance of the two grafts by histological analysis and scanning electron microscopy (SEM). Results: No complications, such as sweating on the graft or significant bleeding from the needle hole site, were seen in the PCL/PDO + 10%DY graft immediately after implantation. Serial ultrasonographic examination and immunohistochemical analysis demonstrated that PCL/PDO + 10%DY grafts showed normal physiological blood flow and minimal lumen reduction, and pulsed synchronously with the native artery at 4 weeks after implantation. However, all e -PTFE grafts occluded within the study period. The luminal surface of the PCL/PDO + 10%DY graft in the transitional zone was fully covered with endothelial cells as observed by SEM. Conclusion: The PCL/PDO + 10%DY graft was well tolerated, and no adverse tissue reaction was observed in porcine carotid models during the short-term follow-up. Colonization of the graft by host endothelial and smooth muscle cells coupled with substantial extracellular matrix production marked the regenerative capability. Thus, this material may be an ideal substitute for vascular reconstruction and bypass surgeries. Long-term observations will be necessary to determine the anti-thrombotic and remodeling potential of this device.

Effect of MMP/TIMP Balancing of Cynoglossus semilaevis Shell Extracts on Skin Protection - Soo-Cheol Choi; In-Ah Lee (Fishes, 2021)
Cynoglossus semilaevis shell is a by-product of the Cynoglossus semilaevis, a species of fish mainly distributed along the west coast of Korea. As its skin is very tough and difficult to process, it is not useful as food. For this reason, most of it is discarded except for a small amount that is used as feed, which results in environmental pollution. Considering this, there is a need for research on the development of functional materials using Cynoglossus semilaevis shell. This study focused on the mechanism of in vitro expression function of Cynoglossus semilaevis shell extract (CSE) for skin tissue in human dermal fibroblasts that induced or did not induce wrinkles by UV-B irradiation and aims to use it as a functional material for human skin beauty or wrinkle improvement through extraction and purification. According to the ELISA results using human dermal fibroblast cells, CSE reduced MMP-1 and elastase activity by up to 21.89% and 12.04%, respectively, in a concentration-dependent manner, and increased PIP synthesis by up to 62.24% in a concentration-dependent manner. The RT-PCR test results using mRNA showed the MMP-1, 2, and 3 expression levels were suppressed in the CSE-treated group compared to the UVB-induced group and caused a concentration-dependent increase in TIMP-1 in the CSE-treat group. These results suggest that CSE can maintain and improve skin tissue conditions through MMP/TIMP balancing in human dermal fibroblast cell lines and indicate its potential as a functional material for improving skin diseases and suppressing photo-aging.

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Clinical factors influencing the performance of bacterial multiplex polymerase chain reaction in patients with community-onset pneumonia - Ga Eun Park; Kyong Ran Peck; Jae-Hoon Ko; Cheol-In Kang; Sun Young Cho; Doo Ryeon Chung; Nam Yong Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

An inverse agonist of estrogen-related receptor γ regulates 2-arachidonoylglycerol synthesis by modulating diacylglycerol lipase expression in alcohol-intoxicated mice - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina kim; Don-Kyu Kim; Ji-Hyeok Lee; Hyunhee Oh; In-Kyu Lee; Wook Kim; Sung Jin Cho; Cheol Soo Choi; Steven Dooley; et al. (Archives of Toxicology, 2020)

Clinical effectiveness of oral antimicrobial therapy for acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Kyoung Ree Lim; Hyunju Lee; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Analysis of Determinants for an Enhanced and Long-lasting Coastal Convective System by Means of a Case Study (26 July 2011) - Jung-Tae Lee; Dong-In Lee; Shingo Shimizu; Cheol-Hwan You (Advances in Atmospheric Sciences, 2019)

Evaluating the optimal dose of teicoplanin with therapeutic drug monitoring: not too high for adverse event, not too low for treatment efficacy - Si-Ho Kim; Cheol-In Kang; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Soo-Youn Lee; Yae-Jean Kim; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Elevated carbon dioxide significantly improves ascorbic acid content, antioxidative properties and restricted biomass production in cruciferous vegetable seedlings - Muthusamy Muthusamy; Jung Eun Hwang; Suk Hee Kim; Jin A. Kim; Mi-Jeong Jeong; Hyeong Cheol Park; Soo In Lee (Plant Biotechnology Reports, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

A discontinuity in the late Pleistocene alluvial deposits, Hwacheon‐ri, Gyeongju, Korea: Occurrences and paleoenvironmental implication - Hoil Lee; In Sung Paik; Hyun Joo Kim; Hee‐Cheol Kang; Won Gyeong Seol; Jin‐Young Lee (Island Arc, 2018)
A sedimentary discontinuity is present in the late Pleistocene alluvial deposits exposed along the cliff in stream side, Gyeongju, Korea. Sedimentological study, Optically Stimulated Luminescence (OSL) age dating, and X‐ray diffraction (XRD), and X‐ray fluorescence spectrometer (XRF) analyses were conducted in order to interpret the origin of the discontinuity surface. Based on the sedimentological study, these deposits can be divided into three distinct stages, in ascending order: (Stage 1) development of a braided stream flowing from south to north and deposition by debris flows from the mountain aside the stream during and/or after deposition of the braided stream; (Stage 2) deposition by intermittent events during a state of stagnation after the abandonment or migration of the previously existed braided stream; and (Stage 3) deposition of gravels from debris flows from the mountain aside the stream. Hornfelsic gravels are common in Stage 1, whereas andesitic gravels are predominant in Stage 3, suggesting the provenance change from Stage 1 to Stage 3. The discontinuity surface is laterally extensive and marked by a distinct carbonaceous dark grey horizon between Stage 2 and Stage 3. It is characteristic that rootlets mineralized by vivianite are present, and iron‐oxide crusts are cutting across irregularly below the discontinuity surface. It is thus interpreted that the shift of depositional environment from an alluvial plain (Stage 2) (125 ka) to an alluvial fan (Stage 3) (94–55 ka) was an alluvial response to sea level change from the interglacial to the glacial. The development of iron‐oxide crusts and diagenetic vivianite in the discontinuity surface suggests humid condition persisted during the paleoclimatic shift from the last interglacial to the last glacial stages.

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Sound wave affects the expression of ethylene biosynthesis-related genes through control of transcription factors RIN and HB-1 - Joo Yeol Kim; Hye Ryun Ahn; Sun Tae Kim; Cheol Woo Min; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2016)

Toluene induces early growth response-1 dependent thymic stromal lymphopoietin expression in human keratinocytes - Hana Lee; Jae Beom Park; Hyu Cheol Bae; Woo-In Ryu; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Whole-transcriptome analysis of mouse adipose tissue in response to short-term caloric restriction - Seung-Soo Kim; Kyung-Mi Choi; Soyoung Kim; Taesun Park; In-Cheol Cho; Jae-Won Lee; Cheol-Koo Lee (Molecular Genetics and Genomics, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Erratum to: Fluorescent Dye Labeled Iron Oxide/Silica Core/Shell Nanoparticle as a Multimodal Imaging Probe - Eue Soon Jang; Seung Yong Lee; Eui-Joon Cha; In-Cheol Sun; Ick Chan Kwon; Dukjoon Kim; Young Il Kim; Kwangmeyung Kim; Cheol-Hee Ahn (Pharmaceutical Research, 2015)

Fluorescent Dye Labeled Iron Oxide/Silica Core/Shell Nanoparticle as a Multimodal Imaging Probe - Eue Soon Jang; Seung Yong Lee; Eui-Joon Cha; In-Cheol Sun; Ick Chan Kwon; Dukjoon Kim; Young Il Kim; Kwangmeyung Kim; Cheol-Hee Ahn (Pharmaceutical Research, 2014)

ZnO nanoparticle induces apoptosis by ROS triggered mitochondrial pathway in human keratinocytes - Woo-In Ryu; Yoon-Hee Park; Hyun Cheol Bae; Jin Hee Kim; Sang Hoon Jeong; Hana Lee; Sang Wook Son (Molecular & Cellular Toxicology, 2014)

Genome-wide association analysis to identify SNP markers affecting teat numbers in an F2 intercross population between Landrace and Korean native pigs - Jae-Bong Lee; Eun-Ji Jung; Hee-Bok Park; Shil Jin; Dong-Won Seo; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee; Hyun-Tae Lim (Molecular Biology Reports, 2014)

Gene expression analysis reveals a functional role for the Ag-NPs-induced Egr-1 transcriptional factor in human keratinocytes - Gyeongmin Yoo; Sang Hoon Jeong; Woo In Ryu; Hana Lee; Jin Hee Kim; Hyun Cheol Bae; Sang Wook Son (Molecular & Cellular Toxicology, 2014)

Occurrences and origins of soft-sediment deformation structures in the late Pleistocene marine terrace deposits of the southeastern coast of Korea - Ho IL Lee; In Sung Paik; Hee Cheol Kang; Jong-Hwa Chun (Geosciences Journal, 2014)

Triterpenoids from Fragaria ananassa calyx and their inhibitory effects on melanogenesis in B16-F10 mouse melanoma cells - Na-Young Song; Jin-Gyeong Cho; Dongmoon Im; Dae-Young Lee; Qian Wu; Woo-Duck Seo; Hee Cheol Kang; Youn-Hyung Lee; Nam-In Baek (Natural Product Research, 2013)

Chloroform induces HIF-1α-dependent VEGF expression in human keratinocytes - Jae Jun Nam; Hana Lee; Hyun Cheol Bae; Jinhee Kim; Sang Hoon Jeong; Woo-In Ryu; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Normative data for neuromuscular assessment of the hand–arm vibration syndrome and its retrospective applications in Korean male workers - Ryeok Ahn; Cheol-In Yoo; Hun Lee; Chang-Sun Sim; Joo Hyun Sung; Jae-Kook Yoon; Song-Woo Shin (International Archives of Occupational and Environmental Health, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Effect of the size and surface charge of silica nanoparticles on cutaneous toxicity - Yoon-Hee Park; Hyun Cheol Bae; Yeonsue Jang; Sang Hoon Jeong; Ha Na Lee; Woo-In Ryu; Min Gun Yoo; Yu-Ri Kim; Meyoung-Kon Kim; Jong Kwon Lee; Jayoung Jeong; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Association of the gene encoding stearoyl-CoA desaturase (SCD) with fatty acid composition in an intercross population between Landrace and Korean native pigs - Dyah Maharani; Hee-Bok Park; Jae-Bong Lee; Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee (Molecular Biology Reports, 2013)

Selenium Significantly Inhibits Adipocyte Hypertrophy and Abdominal Fat Accumulation in OLETF Rats via Induction of Fatty Acid β-Oxidation - Ji Eun Kim; Sun Il Choi; Hye Ryun Lee; In Sik Hwang; Young Ju Lee; Beum Soo An; Sang Hak Lee; Hak Jin Kim; Byeong Cheol Kang; Dae Youn Hwang (Biological Trace Element Research, 2012)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

QTL analysis of back fat thickness and carcass pH in an F2 intercross between Landrace and Korean native pigs - Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; Taeyoung Kang; Jun Heon Lee; Hee-Bok Park; In-Cheol Cho (Molecular Biology Reports, 2012)

Porcine SPP1 gene polymorphism association with phenotypic traits in the Landrace × Jeju (Korea) black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Hong-Shik Oh; In-Cheol Cho (Molecular Biology Reports, 2012)

A promoter polymorphism of MSTN g.−371T>A and its associations with carcass traits in Korean cattle - Sang-Hyun Han; In-Cheol Cho; Moon-Suck Ko; Eun-Young Kim; Se-Pill Park; Sung-Soo Lee; Hong-Shik Oh (Molecular Biology Reports, 2012)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

Nematicidal Activity of a Nonpathogenic Biocontrol Bacterium, Pseudomonas chlororaphis O6 - Jang Hoon Lee; Kyung Cheol Ma; Sug Ju Ko; Beom Ryong Kang; In Seon Kim; Young Cheol Kim (Current Microbiology, 2011)

Soft‐sediment deformation structures in Cretaceous non‐marine deposits of southeastern Gyeongsang Basin, Korea: Occurrences and origin - Hee‐Cheol Kang; In Sung Paik; Ho Il Lee; Jeong Eun Lee; Jong‐Hwa Chun (Island Arc, 2010)
A variety of soft‐sediment deformation structures formed during or shortly after deposition occurs in the Cretaceous Seongpori and Dadaepo Formations of the southeastern Gyeongsang Basin exposed along coastal areas of southeastern Korean Peninsula for 0.5–2 km. These are mostly present in a fluvial plain facies, with interbedded lacustrine deposits. In this study, the features of different kinds of soft‐sediment deformation structures have been interpreted on the basis of sedimentology of structure‐bearing deposits, comparison with normal sedimentary structures, timing and mechanism of deformation, and triggering mechanisms. The soft‐sediment deformation structures can be classified into four morphological groups: (i) load structures (load casts, ball‐and‐pillow structures); (ii) soft‐sediment intrusive structures (dish‐and‐pillars, clastic dykes, sills); (iii) ductile disturbed structures (convolute folds, slump structures); and (iv) brittle deformation structures (syndepositional faulting, dislocated breccia). The most probable triggering mechanisms resulting in these structures were seismic shocks. These interpretations are based on the following field observations: (i) location of the study area within tectonically active fault zone reactivated several times during the Cretaceous; (ii) deformation structures confined to single stratigraphic levels; (iii) lateral continuity and occurrences of various soft‐sediment deformation structures in the deformed level over large areas; (iv) absence of depositional slope to indicate gravity sliding or slumping; and (v) similarity to the structures produced experimentally. The soft‐sediment deformation structures in the study areas are thus interpreted to have been generated by seismic shocks with an estimated magnitude of M > 5, representing an intermittent record of the active tectonic and sedimentary processes during the development and evolution of two formations from the late Early Cretaceous to the Late Cretaceous.

Detection of replicating negative-sense RNAs in CaCo-2 cells infected with human astrovirus - So Young Jang; Weon Hwa Jeong; Mi Suk Kim; Young Min Lee; Jae In Lee; Gyu Cheol Lee; Soon Young Paik; Gwang Pyo Koh; Jong Min Kim; Chan Hee Lee (Archives of Virology, 2010)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

A new strain of Arthrinium phaeospermum isolated from Carex kobomugi Ohwi is capable of gibberellin production - Sumera Afzal Khan; Muhammad Hamayun; Ho-youn Kim; Hyeok-jun Yoon; Jong-cheol Seo; Yeon-sik Choo; In-jung Lee; Sang-dal Kim; In-koo Rhee; Jong-guk Kim (Biotechnology Letters, 2009)

AGHR polymorphism and its associations with carcass traits in Harrwoo cattle - Sang-Hyun Han; In-Cheol Cho; Jin-Hyoung Kim; Moon-Suck Ko; Ha-Yeon Jeong; Hong-Shik Oh; Sung-Soo Lee (Genes & Genomics, 2009)

Influence of TGF-β1 on the expression of BSP, DSP, TGF-β1 receptor I and Smad proteins during reparative dentinogenesis - Yun-Chan Hwang; In-Nam Hwang; Won-Mann Oh; Joo-Cheol Park; Dong-Seol Lee; Ho-Hyun Son (Journal of Molecular Histology, 2008)

Isolation and structural analysis of bamylocin A, novel lipopeptide from Bacillus amyloliquefaciens LP03 having antagonistic and crude oil-emulsifying activity - Sang-Cheol Lee; Sun-Hee Kim; In-Hye Park; Soo-Yeol Chung; Yong-Lark Choi (Archives of Microbiology, 2007)

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling - Min-Ju Chae; Jung-Sook Lee; Myung-Hee Nam; Kun Cho; Ji-Yeon Hong; Sang-A Yi; Seok-Cheol Suh; In-Sun Yoon (Plant Molecular Biology, 2006)

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

Lidocaine hydrochloride-sodium bicarbonate as an anesthetic for soft-shelled turtle Pelodiscus sinensis - In-Seok PARK; Sung Hwoan CHO; Jun Wook HUR; Gyeng-Cheol CHOI; Sung-Yong OH; Dong Soo KIM; Jae-Seong LEE (Fisheries Science, 2006)

cDNA isolation and characterization of (+)-germacrene a synthase fromIxerls dentata form.albiflora Hara - Min-Young Kim; Yung-Jin Chang; Myun-Ho Bang; Nam-In Baek; Jianming Jin; Cheol-Ho Lee; Soo-Un Kim (Journal of Plant Biology, 2005)

Co-expression of a Modified Maize Ribosome-inactivating Protein and a Rice Basic Chitinase Gene in Transgenic Rice Plants Confers Enhanced Resistance to Sheath Blight - Ju-Kon Kim; In-Cheol Jang; Ray Wu; Wei-Neng Zuo; Rebecca S. Boston; Yong-Hwan Lee; Il-Pyung Ahn; Baek Hie Nahm (Transgenic Research, 2003)

Design and biological activity of synthetic oligopeptides with Pro-His-Ser-Arg-Asn (PHSRN) and Arg-Gly-Asp (RGD) motifs for human osteoblast-like cell (MG-63) adhesion - Tae-Il Kim; Jun-Hyeog Jang; Yong-Moo Lee; In-Cheol Ryu; Chong-Pyoung Chung; Soo-Boo Han; Sang-Mook Choi; Young Ku (Biotechnology Letters, 2002)

Light- and electron-microscopic analysis of neuropeptide Y-immunoreactive amacrine cells in the guinea pig retina - Wha-Sun Kang; Min-Young Lim; Eun-Jin Lee; In-Beom Kim; Su-Ja Oh; Nicholas C. Brecha; Cheol-Beom Park; Myung-Hoon Chun (Cell and Tissue Research, 2001)

Stimulation of β-carotene synthesis by hydrogen peroxide in Blakeslea trispora - Jae-Cheol Jeong; In-Young Lee; Seon-Won Kim; Young-Hoon Park (Biotechnology Letters, 1999)